The neoglycolipid (NGL) technology‐based microarrays and future prospects. Issue 23 (29th August 2018) - Li, Zhen; Feizi, Ten
Abstract : The neoglycolipid (NGL) technology is the basis of a state‐of‐the‐art oligosaccharide microarray system, which we offer for screening analyses to the broad scientific community. We review here the sequential development of the technology and its power in pinpointing and isolating naturally occurring ligands for glycan‐binding proteins (GBPs) within glycan populations. We highlight our Designer Array approach and Beam Search Array approach for generating natural glycome arrays to identify novel ligands of biological relevance. These two microarray approaches have been applied for assignments of ligands or antigens on glucan polysaccharides for effector proteins of the immune system (Dectin‐1, DC‐SIGN and DC‐SIGNR) and carbohydrate‐binding modules (CBMs) on bacterial hydrolases. We also discuss here the more recent applications to elucidate the structure of a prostate cancer‐ associated antigen F77 and identify ligands for adhesins of two rotaviruses, P[10] and P[19], expressed on an epithelial mucin glycoprotein. Abstract :